Systematic Requirements Management - Essential factors when managing requirements in major infrastructure projects - Brandes, Olivia; Cesar, Emelie (My University, 2022)
Introduction - One essential criteria for major infrastructure projects to be successful is to fulfill the needs and expectations of a project, which are defined as requirements. Currently, major infrastructure projects have difficulties in achieving requirements where one main reason is the increased number of requirements. Accordingly, there is a need to establish an integrated process for systematic requirements management (SRM) to fulfill the requirements. Therefore, the aim of the study was to investigate what changes are required to establish SRM in major infrastructure projects. Method - A case study was conducted at major projects west at Skanska in Sweden. The study was based on a qualitative research consisting of 16 interviews. The interviews aimed to investigate the organisation´s current process and tools for requirements management (RM). A literature study was conducted to establish a theoretical foundation to the case study. Empirical Study - The studied organisation has a lack of SRM within their projects, even though both design and production works systematically to some extent. Therefore, the collaboration within SRM between these project phases need to be extended. In addition, seven challenges connected to countermeasures were identified within SRM: increased number of requirements, unclear requirements, changes of requirements, lack of common structure, negative attitude, negative reputation and difficulties in documentation. Furthermore, RM tools have been identified as essential when establishing SRM. Conclusion - To facilitate the establishment of SRM, it is important that organisations, in an early project stage, creates an integrated and common structure, including working approaches, routines and RM tools for SRM. The management has a central role to implement and maintain the common structure as well as motivate employees to understand how and why SRM should be applied. To motivate employees, it is essential to create a positive attitude, improving the understanding and establishing organisational routines. Organisations need to consider the correlation between IT, people, management and structure, and their impact on SRM. Hence, all four factors are essential when establishing an integrated process for SRM throughout all project phases, and thus achieve client satisfaction.